Rhus coriaria L. (Sumac) Evokes Endothelium-Dependent Vasorelaxation of Rat Aorta: Involvement of the cAMP and cGMP Pathways - Anwar, Mohammad A.; Samaha, Ali A.; Baydoun, Safaa; Iratni, Rabah; Eid, Ali H. (Frontiers in Pharmacology, 2018)
Rhus coriaria L. (sumac) is widely used in traditional remedies and cuisine of countries of the Mediterranean as well as central and south-west Asia. Administration of sumac to experimental models and patients with diverse pathological conditions generates multi-faceted propitious effects, including the quality as a vasodilator. Together, the effects are concertedly channeled towards cardiovasobolic protection. However, there is paucity of data on the mechanism of action for sumac’s vasodilatory effect, an attribute which is considered to be advantageous for unhealthy circulatory system. Accordingly, we sought to determine the mechanisms by which sumac elicits its vasorelaxatory effects. We deciphered the signaling networks by application of a range of pharmacological inhibitors, biochemical assays and including the quantification of cyclic nucleotide monophosphates. Herein, we provide evidence that an ethanolic extract of sumac fruit, dose-dependently, relaxes rat isolated aorta. The mechanistic effect is achieved via stimulation of multiple transducers namely PI3-K/Akt, eNOS, NO, guanylyl cyclase, cGMP, and PKG. Interestingly, the arachidonic acid pathway (cyclooxygenases), adenylyl cyclase/cAMP and ATP-dependent potassium channels appear to partake in this sumac-orchestrated attenuation of vascular tone. Clearly, our data support the favorable potential cardio-vasculoprotective action of sumac.